Fanaticism, Korean Wave, Brand Ambassadors, and Product Quality Affect Customer Satisfaction of Nacific K-Beauty Products - Tania Permata Yanra; Andala Rama Putra Barusman (Green Inflation: International Journal of Management and Strategic Business Leadership, 2026)
The study try to investigate what influences ATINY, followers of the South Korean idol group ATEEZ, about customer satisfaction and their decision to buy Nacific products. It investigates how brand ambassadors, fanaticism, Korean Wave, product quality, and buying decisions affect consumer pleasure. Through the use of questionnaires, 396 members of the ATINY fan group participated in the study. Structural Equation Modeling (SEM) was used in the study to analyze the data. The findings show that consumer happiness and purchasing decisions are influenced by product quality. Fanaticism, the Korean Wave, and brand ambassadors, however, had negligible effects on consumer happiness and purchase decisions. Additionally, it has been demonstrated that purchase decisions significantly and favorably affect consumer satisfaction. The study recommends that future studies examine the impact of social media and influencers on consumer behavior and take into account other factors like brand trust or customer experience. Additionally, studies using larger samples from different demographic groups can yield more broadly applicable findings.